Leveraging AI-enabled personalization in customer relationship management - Karppanen, Vili (2024)
Customer relationship management (CRM) became an important topic in both research and companies due to technological advancements such as the World Wide Web and innovations in customer database and data warehouse technologies. In today's competitive business landscape, where companies are seeking new ways to differentiate themselves from competitors, one strategy is to implement an individualized CRM strategy that treats customers as unique individuals and relies on effective personalization. This thesis explores the role of personalization in CRM and how AI can enhance personalization. Especially generative AI’s effect on customer acquisition through creation of personalized content will be examined. Using the Stimulus-Organism-Response (SOR) framework, it is hypothesized that generative AI-personalized content (stimulus) influences perceived personalization, perceived value, and satisfaction (organisms), which then lead to purchase intentions (response). A quantitative methodology was adopted, collecting data from 65 participants through an online survey administered in Finnish. The findings indicate that generative AI-personalized content has a stronger impact on perceived personalization compared to non-personalized content, implying that generative AI can effectively be used in the personalization of marketing communications. Moreover, results suggest that perceived personalization enhances perceived value of the content, which in turn, positively affects customer satisfaction. Lastly, the results indicate that customer satisfaction has a positive relationship with purchase intentions. The study also identifies the role of involvement as a control variable influencing purchase intention. Based on this study, leveraging AI for personalization process can facilitate customer relationship initiation.